Sosialisasi Panduan Penerapan Sistem Pemeliharaan Berkelanjutan pada Rumah Tinggal Sederhana - Wisdianti, Dara; Fitri, Rahmadhani (MARHALADO: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service program aims to increase the capacity of residents in implementing a sustainable home maintenance system for simple residential houses (RTS). The activity was carried out in Medan City, in collaboration with the local residential community and the Green Building Council Indonesia (GBCI). The background of this activity is the continued dominance of reactive home maintenance patterns, low energy and water efficiency, as well as the declining quality of health and residential comfort due to the lack of planned maintenance in RTS, which are generally over 10 years old. The main problems faced by the partners include the limited guidelines for integrating green building concepts with systematic and sustainable home maintenance, the perception that home maintenance requires high costs, and the unavailability of practical guidelines that are easy to understand and apply. On the other hand, the green building concept is still perceived as an expensive concept that is only relevant for new buildings, thus it has not been integrated into the maintenance of existing homes. This program offers an educational and participatory solution through a participatory home audit using the 10-Point Green Home Maintenance Checklist based on the GBCI GREEN HOMES principles. The targeted outputs include the availability of replicable maintenance guidelines and modules. This program is expected to reduce minor house damage, improve energy and water efficiency, and support the creation of healthier and more sustainable housing at the community level.